Association between the severity of acquired von Willebrand syndrome and gastrointestinal bleeding after continuous-flow left ventricular assist device implantation. (8th May 2018) - Sakatsume, Ko; Saito, Kenki; Akiyama, Masatoshi; Sasaki, Konosuke; Kawatsu, Satoshi; Takahashi, Goro; Adachi, Osamu; Kawamoto, Shunsuke; Horiuchi, Hisanori; Saiki, Yoshikatsu
Abstract: OBJECTIVES: Acquired von Willebrand syndrome, characterized by the reduction in von Willebrand factor (vWF) large multimers, has recently been considered as one of the causes of gastrointestinal bleeding (GIB). It remains unclear whether its haematological severity is linked with susceptibility to bleeding because the definition of the haematological severity of acquired von Willebrand syndrome has not been precisely determined. This study sought to establish a quantitative methodology to assess the haematological severity of acquired von Willebrand syndrome and to define the threshold for occurrence of GIB in patients implanted with left ventricular assist devices (LVADs). METHODS: In total, 41 patients treated with continuous-flow LVAD implanted between 2011 and 2017 at Tohoku University Hospital were investigated. vWF large multimers were quantitatively evaluated using the 'vWF large multimer index' defined as the ratio of a large multimer proportion in total vWF derived from a patient to that from a normal control. Using this index, the amount of vWF large multimers was expressed as a percentage of its normal control value obtained with a simultaneous analysis of each time measurement. RESULTS: Twelve (29%) patients developed GIB events during follow-up periods (median 591 days) after an LVAD implantation. The vWF large multimer index in patients with GIB was significantly lower than that in those without GIB (25.0 ± 10.3% vs 37.5 ± 17.8%, P = 0.008). Most importantly, all patients experiencing GIB exhibited a vWF large multimer index below 40%. CONCLUSIONS: Patients with GIB exhibited a more severe loss of vWF large multimers. The vWF large multimer index may dictate the risk of GIB after an LVAD implantation. Clinical trial registration number: UMIN000018135.